Cation exchange in a fluorescent zinc-based metal–organic framework for cadmium ion detection. Issue 42 (12th October 2021) - Chen, Mao-Long; Qi, Zhen-Li; Jin, Wan-Ting; Xu, Zhou; Cheng, Yun-Hui; Zhou, Zhao-Hui
Abstract : A Zn metal–organic framework with a large aperture shows remarkable fluorescence characteristics for the detection of cadmium ions in aqueous solution and can adsorb CO2 and O2 selectively. Abstract : The anion zinc-based metal–organic framework [HDMA]2 n [Zn2 n (DMA)2 n (1, 4-BDC)3 n ]·2 n DMF·6 n H2 O (1, DMF = N, N -dimethylformamide, 1, 4-H2 BDC = 1, 4-benzenedicarboxylic acid, DMA = dimethylamine) with open channels has been used as a luminescent sensor for Cd 2+ detection, and was obtained by solvothermal synthesis and fully characterized. It shows excellent fluorescence stability in aqueous solution, which was further enhanced with a remarkable fluorescence shift upon introduction of Cd 2+, while negligible effects occurred for Fe 2+, Zn 2+, Fe 3+, Cu 2+, Co 2+, Ni 2+, Mn 2+ and Pb 2+, respectively. The detection limit is 9.9 μM with a linear range between 50 and 600 μM for Cd 2+ . Furthermore, it can be used to detect Cd 2+ in tap water and rice samples directly. Solid state 13 C NMR spectra give direct evidence for the ion exchange between protonated dimethylamine and Cd 2+ hydrates, which results in the increase of fluorescence and blue shift of the wavelength. The coordination of Cd 2+ with the carboxyl groups of 1 in the interface of nano-channels can be also observed using IR spectra, where a structural model has been suggested in the confined channels. This may provide a new construction method for anion fluorescent MOF materials, where a confined sample has obvious influence on the detection of Cd 2+ . The maximum adsorption capacities are 10.36, 54.53, 103.06 and 8.78 mg g −1 for CH4, CO2, O2 and N2 at 30 bar respectively.